The taxonomic status of Tilia dasystyla in Crimea, Ukraine - Pigott, C. D.; Francis, B. (Edinburgh Journal of Botany, 1999)
Nine populations of Tilia dasystyla Steven (Tiliaceae) in the Crimean mountains (Krymskiye Gory), including the type locality at Kastel Dag, were studied in the field and sampled by collection of herbarium specimens. This material was compared with specimens referred to Tilia hegonifolia Steven collected in Crimea, the Caucasus and Iran. Measurements or scores of 21 morphological characters made on the dried material were analysed by principal components analysis and logistic regression. These analyses demonstrated that the majority of trees could be correctly allocated to either Crimea or the Caucasus and Iran on the basis of the shape of their leaves and the area of their bracts. In addition there are differences of leaf and bract texture and bract colour which can be observed in fresh material. Chromosome counts showed that Crimean trees and one Caucasian tree are tetraploid (2n = 164). It is proposed that the Crimean, Caucasian and Iranian trees be treated as a single species with at least two subspecies: Tilia dasystyla Steven subsp. dasystyla from Crimea and T. dasystyla Steven subsp. caucasica (V. Engl.) Pigott from the Caucasus and Iran.